Highly efficient Cesium Titanium (IV) Bromide perovskite solar cell and its point defect investigation: A computational study - Khan, Md. Abdul Kaium; Urmi, Sadia Sultana; Ferdous, Tasnim Tareq; Azam, Sakibul; Alim, Mohammad Abdul (Superlattices and microstructures, 2021)
Lead-free, halide-based perovskites are drawing appreciable attention for solar cell applications due to the non-toxic nature and stable performance in ambient environment. In this study, we investigated different facets of a Cesium Titanium (IV) Bromide (Cs2TiBr6) perovskite solar cell (PSC) with ZnO and MoO3 as charge transport materials. Upon numerical optimization of perovskite layer thickness, its defect density, and the interface defect density, we propose a highly efficient, practically realizable PSC with a power conversion efficiency of 18.15%. Besides, we investigated different point defects in Cs2TiBr6 and the effect of their electronic band positions on the PSC performance. It is found that for Cs2TiBr6 based PSC applications, the material processing of Cs2TiBr6 is a crucial aspect and the PSC may underperform for deep defect states (0.2 eV ~ 1.6 eV) with defect density over 1015 cm−3. In addition, we analyzed different back contact materials and found that carbon-based back contact can be a low-cost solution to gold for Cs2TiBr6 PSCs. •A Cesium Titanium (IV) Bromide (Cs2TiBr6) based perovskite solar cell with FTO/ZnO/Cs2TiBr6/MoO3/Au structure is proposed.•An optimum power conversion efficiency (PCE) of 18.15% is achieved.•Investigation on possible point defects in Cs2TiBr6 and their electronic band position's effect on the PSC performance.•For deep defect state (0.2 eV ~ 1.6 eV) and defect density over 1015 cm−3, the PSC tends to underperform.•Carbon-based back contact can be a possible low cost replacement of gold for Cs2TiBr6 PSCs.